THE INFLUENCE OF INSTRUCTIONAL VIDEO MEDIA ON STUDENT LEARNING OUTCOMES IN CLASS IV SUBJECTS SBdP AT SDN TONDO - Surahman J Wilade; Yun Ratna Lagandesa; Margaret Maharani Bode (Jurnal Dikdas, 2021)
Video learning media is an alternative that can increase student participation in learning, so that students can think actively. The formulation of the research problem is how the student learning outcomes using video media and student learning outcomes who do not use video media at SDN Tondo. Are there differences in student learning outcomes taught using video media with student learning outcomes taught not using video at SDN Tondo. How do students respond to learning using video media and student responses who do not use video media at SDN Tondo. The results showed that the learning outcomes of the experimental and control classes were categorized as very high, where the percentage of the experimental class was 86.63% and the control class was 77.53%. There are differences in the learning outcomes of the experimental and control classes in SBdP subjects, it can be seen with the sig-value t-test. (2-tailed) for the experimental class of 0.014, greater than the significance level of 0.005 (0.014> 0.005) as well as the sig results. (2-tailed) for the control class of 0.018, which is greater than the significance level of 0.005 (0.018> 0.005), which means that these two have significant differences. The t value of the Experiment class is 2.545, which is greater than the t table (1.70562) as well as the t value of the Control class, which is 2.467, which is greater than the t table (1.71714), meaning that there is a significant difference. Thus it can be concluded that H0 is rejected and H1 is accepted. From the research results, it was concluded that learning using video media could affect student learning outcomes in SBdP subjects in class IV SDN Tondo.